Loddon Mallee healthcare worker COVID-19 study—protocol for a prospective cohort study examining the health and well-being of rural Australian healthcare workers during the COVID-19 pandemic - Stephen Begg; Mark McEvoy; Timothy C Skinner; Carol Parker; Angela Crombie; Peter Faulkner; Anne McEvoy; Laura Bamforth; Gabriel Caccaviello (BMJ Open)
Introduction The COVID-19 pandemic is creating immense psychosocial disturbance. While global, broad-based research is being conducted, little is known about the effects of the COVID-19 pandemic on health and well-being or how protective and resilience factors influence the human response in Australian rural and regional communities. Rural and regional communities often have less resources to deal with such public health emergencies and face additional environmental adversity. Healthcare workers, including those in rural and regional areas, have felt the immediate impacts of COVID-19 in a multitude of ways and these impacts will continue for years to come. Therefore, this study aims to describe and understand the impacts of the COVID-19 pandemic on the rural and regional healthcare workforce within the Loddon Mallee region, Victoria, Australia.Methods and analysis This prospective cohort of rural and regional healthcare workers will be recruited and followed over 3 years to examine the effects of the COVID-19 pandemic on their health and well-being. Self-administered online questionnaires will be administered every 6 months for a 36-month period. Multiple outcomes will be assessed; however, the primary outcomes are emotional health and well-being and psychological resilience. Emotional health and well-being will be measured using validated instruments that will assess multiple domains of the emotional health and well-being continuum.Linear and logistic regression and latent growth curve modelling will be used to examine the association between baseline and follow-up participant emotional health, well-being and resilience while adjusting for potentially time-varying confounding variables. Participant characteristics measured at baseline will also be tested for association with incident health, morbidity, mortality and health service utilisation outcomes at follow-up.Ethics and dissemination Ethical approval has been obtained through the Bendigo Health Human Research Ethics Committee. The study findings will be disseminated through international conferences, international peer-reviewed journals and social media.Trial registration number ACTRN12620001269921.